2019
DOI: 10.1182/blood.2019001043
|View full text |Cite
|
Sign up to set email alerts
|

A novel model of controlling PD-L1 expression in ALK+ anaplastic large cell lymphoma revealed by CRISPR screening

Abstract: The success of programmed cell death protein 1 (PD-1)/PD-L1-based immunotherapy highlights the critical role played by PD-L1 in cancer progression and reveals an urgent need to develop new approaches to attenuate PD-L1 function by gaining insight into how its expression is controlled. Anaplastic lymphoma kinase (ALK)-positive anaplastic large-cell lymphoma (ALK+ ALCL) expresses a high level of PD-L1 as a result of the constitutive activation of multiple oncogenic signaling pathways downstream of ALK activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 46 publications
(46 reference statements)
0
48
0
Order By: Relevance
“…These data indicate that PD-L1 expression is dependent on PI3Kδ activity in B-CLL cells. Remarkably, a recent study has shown a dependence of PD-L1 expression on the PI3K/Akt signaling pathway in anaplastic large cell lymphoma 47 .…”
Section: Discussionmentioning
confidence: 98%
“…These data indicate that PD-L1 expression is dependent on PI3Kδ activity in B-CLL cells. Remarkably, a recent study has shown a dependence of PD-L1 expression on the PI3K/Akt signaling pathway in anaplastic large cell lymphoma 47 .…”
Section: Discussionmentioning
confidence: 98%
“…Aberrant activities of AP1 TFs including JUN, JUNB and BATF3 are an additional ALCL hallmark [26]. Moreover, BATF3 is a target gene of STAT3 [27], demonstrating close regulatory relationships between these oncogenes in ALCL. Expression profiling analysis indicated that primary ALCL cells express several TH17 signature genes [28].…”
Section: Research Papermentioning
confidence: 99%
“…Signaling pathways that are intrinsically activated and responsible for the expression of PD-L1 are ill defined in this subtype and include SVs of PD-L1 in 15% of EBV positive cases, caused by a truncation of the 3′-untranslated region [ 93 ]. PD-L1 is upregulated in anaplastic large cell lymphoma (ALCL), and novel mechanisms of PD-L1 regulation and expression have been discovered in anaplastic lymphoma kinase- (ALK-) positive and ALK-negative subtypes of the disease [ 134 , 135 ]. Natural killer/T-cell lymphomas (NKTCL) are invariably infected with EBV, and EBV-infected lymphoma cells upregulate PD-L1 expression [ 37 ].…”
Section: Peripheral T Cell Lymphomas (Ptcl)mentioning
confidence: 99%